Genotypic Characterization of Vibrio Sp. Isolated from Cockles Obtained in Padang, Indonesia - Yaakub, Zulkifli (2006)
Vibrio parahaemoi'yticus is a gram negative bacterium that naturally found in warm marine environments. They commonly live in shellfish, oysters and cockles and cause gastrointestinal illness in humans. Most people become infected by eating raw or undercooked shellfish. In this study, 32 isolates of V: parahaemolyticus were isolated Erom cockles obtained from Padang, Indonesia. Presumptive identification of the isolates was performed by the following analysis: antibiotic resistance, plasmid profiling, specific PCR, random amplified polymorphic DNA (RAPD)-PCR and enternbacterial repetitive intergenic consensus (ERIC)-PCR. In the antibiotic resistance test, 16 types of antibiotics were tested against this bacterium. The isolates of V: parahemolyticus showed variable antibiotic resistance pattern. They are most commonly resistant to amoxycillin, bacitracin, penicillin, teicoplanin, ampicillin and carbenicillin. In the plasmid profiling analysis, 14 different profiles were determined. The most common profiles for the isolates is profile 110.2 which contains 4 plasmids with 5.6,7.2,42.4 and 54.0 kilobase pairs respectively. For toxR detection, all of the isolates were positive but they gave negative results in both tdh and trh detection. This indicated that they have less potential to cause diseases. They also showed high diversity in RAPD-PCR and also ERIC-PCR analysis. They showed many differences in the polymorphism pattern and can be divided into 5 major clusters in RAPD-PCR and 4 major clusters in ERIC-PCR. Application of phenotype and genotype based methods provides information about distribution, epidemiology and pathogenesis of V. parasympathetics. The data is important to identify sources of infection of this bacterium in the case of outbreaks occurrence in humans. This study also gives us preliminary information in monitoring the potential infection risk. It also can increase our awareness about the infection potential of these bacteria.